Is PEP prescribed appropriately?. Issue 8 (September 2015) - Whitlock, G; Nwokolo, N; McOwan, A
<x xml:space="preserve">Abstract</x> We describe the characteristics of HIV post‐exposure prophylaxis (PEP) recipients and PEP indications at 56 Dean Street, a central London sexual health clinic. PEP was prescribed on 577 occasions. Most (97%) was given for unprotected anal intercourse. Over a fifth of exposures involved recreational drug use. Of the patients prescribed PEP, 5.9% were given PEP more than once in this period. As a snapshot of HIV risk behaviour, we note the prevalence of drug use, sex without condom use and group sex among PEP recipients.